Strategi Perbankan Indonesia dalam Menanggulangi Tindak Pidana Pencucian Uang - Hartanti, Juwita Dwi; Kaniyawati, Sinta; Febriyanti, Elvira (Media Hukum Indonesia (MHI), 2024)
The practice of manipulating the assets of criminals, especially monetary assets obtained through criminal activities, to appear to originate from legitimate sources is known as money laundering. The bank plays a strategic role as a target or place to commit crimes, such as money laundering. In Indonesia, TPPU is regulated by a number of laws and regulations, including Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering. This study is a normative legal study that uses a case-based conceptual framework, legislative methods, and descriptive analysis. The purpose of this study is to identify and evaluate the TPPU laws applicable in Indonesia and the tactics used by Indonesian banks to combat TPPU. The findings of this study indicate that banks need to implement CDD and EDD policies. Banks must identify, confirm, and track transactions as part of the Client Due Diligence (CDD) process to ensure that the transactions are in accordance with the client's profile. As an anti-tipping off implementer, banks must maintain the confidentiality of information provided to customers when carrying out banking activities, especially when reporting suspicious financial transactions. Banks must have an information management system that facilitates monitoring and analysis of suspicious finances while supporting money laundering prevention efforts.